Construct Validity and Reliability of the Children Participation Assessment Scale-Child version in Children with Physical Disabilities - Rostamzadeh, Omid; Amini, Malek; Hassani Mehraban, Afsoon (Iranian Journal of Child Neurology, 2021)
Objective This study was conducted to determine the construct validity and reliability of the Children Participation Assessment Scale in activities outside of School–Child version (CPAS-C) in 6-12-year-old children with physical disabilities (PDs) Materials & Methods In this methodological study, participants were 100 children with PDs, recruited from a school for exceptional children with physical-motor disabilities and 100 normally developing children. For assessing the test-retest reliability (ICC), 40 children with PDs completed CPAS-Cwithin a two-week interval, and for assessing the internal consistency (Cronbach’s alpha) and construct validity, 100 children with PDs separately completed the Vinland Adaptive Behavioral Scale (VABS) and CPAS-C. Result The majority of participants were children with CP, among whom the highest and lowest ratios were related to diplegia (32%) and dystonia (1%), respectively. The results showed that CPAS-C had acceptable reliability (ICC: 0.6-0.99). Cronbach’s α score was between weak to moderate (α = 0.25-0.75). The difference in the score of participation between the two groups (normally developing children and children with physical disabilities) was significant in all areas (P<0.001). Conclusion The CPAS-C had acceptable psychometric properties; it can be used as a valid and reliable tool for assessing the participation of 6-12-yearold children with PDs in school activities